2016
DOI: 10.1128/aac.01030-16
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing for Detecting Antimicrobial Resistance in Nontyphoidal Salmonella

Abstract: b Laboratory-based in vitro antimicrobial susceptibility testing is the foundation for guiding anti-infective therapy and monitoring antimicrobial resistance trends. We used whole-genome sequencing (WGS) technology to identify known antimicrobial resistance determinants among strains of nontyphoidal Salmonella and correlated these with susceptibility phenotypes to evaluate the utility of WGS for antimicrobial resistance surveillance. Six hundred forty Salmonella of 43 different serotypes were selected from amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
268
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 324 publications
(299 citation statements)
references
References 31 publications
26
268
1
4
Order By: Relevance
“…An additional 81 Salmonella isolates from retail meats isolated from 2002 to 2011 were included in this study based on the presentation of rare MICs, resulting in a total of 1,738 isolates (see Materials and Methods). This builds on a prior analysis we had conducted in which we compared resistance genotypes and phenotypes for 640 Salmonella isolates (12). In this study, we measured the correlation of specific MICs with the presence of resistance genes as defined in the ResFinder database (17).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional 81 Salmonella isolates from retail meats isolated from 2002 to 2011 were included in this study based on the presentation of rare MICs, resulting in a total of 1,738 isolates (see Materials and Methods). This builds on a prior analysis we had conducted in which we compared resistance genotypes and phenotypes for 640 Salmonella isolates (12). In this study, we measured the correlation of specific MICs with the presence of resistance genes as defined in the ResFinder database (17).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 1,738 Salmonella isolates were isolated in the United States from 40 states from retail meat (1,297), food animal (337), and human (104) sources; these included 640 isolates from a prior analysis (12). Retail meat isolates were from 2002 to 2015, food animal isolates from 2014, and human isolates from 2011 to 2012.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study reported here demonstrates that in silico AMR gene predictions are highly correlated with phenotypic resistance in Salmonella enterica Typhimurium, Newport, and Dublin, as AMR genotype correlated with AMR phenotype with an overall sensitivity and specificity of 97.2 and 85.2%, respectively. The ability to predict AMR phenotype from WGS data with high sensitivity and specificity has previously been observed in Salmonella enterica isolated from humans and retail meats (27) and S. Typhimurium from swine (28), as well as in other organisms, including Staphylococcus aureus (29,30) Campylobacter spp. (31), and Mycobacterium tuberculosis (30).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, correlation between the extrapolated genotype and phenotype is promising and the epidemiological information generated on genetic mechanisms is valuable 8,9 . Reports suggest that inferring antibiotic resistance from genotype results in an overestimation of resistance, possibly due to the presence of silent genes or poorly understood mechan- That is, facilitating the appropriate antimicrobial management of gonorrhoea in an era of increasing resistance to prevent treatment failure, timely provision of an accurate diagnosis to inform appropriate treatment, and providing molecular insights to better understand gonococcal transmission (Table 1).…”
Section: O R E O U T B R E a K S S O L V E D F E W E R C A S E S Pmentioning
confidence: 99%